2020
DOI: 10.1038/s41598-020-78243-z
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower inflorescences absorb maximum light energy if they face east and afternoons are cloudier than mornings

Abstract: The mature inflorescence of sunflowers (Helianthus annuus) orients eastward after its anthesis (the flowering period, especially the maturing of the stamens), from which point it no longer tracks the Sun. Although several hypothetical explanations have been proposed for the ecological functions of this east facing, none have been tested. Here we propose an atmospheric-optical explanation. Using (i) astronomical data of the celestial motion of the Sun, (ii) meteorological data of diurnal cloudiness for Boone Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…We found that the average azimuth of inflorescences is approximately east instead of the azimuth of sunrise. This finding experimentally corroborates the earlier theoretical prediction that the energetically ideal azimuth of sunflower inflorescences is east if mornings are generally less cloudy than afternoons, which is typical for the domestication region of H. annuus ( Horváth et al, 2020 ).…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that the average azimuth of inflorescences is approximately east instead of the azimuth of sunrise. This finding experimentally corroborates the earlier theoretical prediction that the energetically ideal azimuth of sunflower inflorescences is east if mornings are generally less cloudy than afternoons, which is typical for the domestication region of H. annuus ( Horváth et al, 2020 ).…”
Section: Introductionsupporting
confidence: 90%
“…To explain the phenomenon of the southern orientation of a group of sunflowers shadowed for 5 h both after sunrise and before sunset, we used the computer program developed by Horváth et al (2020) . This software computes the total light energy e per unit area absorbed by a sunflower inflorescence between anthesis (1 July) and senescence (7 September) as a function of the azimuth angle α of its normal vector for the typical cloud conditions of a given region, in our present case for Hungary, where mornings are less cloudy than afternoons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations